REWARDING CIVILITY IN CANADA’S BATTLE OF THE BOOKS: CANADA READS AND THE POLITE DISCOURSE OF ELIMINATION - Haynes, Jeremy (My University, 2019)
This thesis looks at three seasons of the Canadian Broadcasting Corporation’s (CBC) radio show Canada Reads – 2014, 2015, and 2016. I examine how each year’s debates over reconciliation (2014), inclusive multiculturalism (2015), and Canada’s role as a global refuge (2016) commonly presume a national mythology that Indigenous peoples have either disappeared or become “Canadian.” I argue that despite the show’s desire to build a better society through encouraging Canadians to read Canadian books, the debates featured on Canada Reads reflect the way assumed Canadian control of Indigenous lands is embedded in the language of Canadian literature and culture to both limit the political disruptiveness of Indigenous presence and reproduce ongoing colonial domination. Central to my argument is the sad truth that, even as the show invites diverse critiques of Canadian society, it nonetheless favours stereotypical narratives of Canadian multiculturalism, benevolence, and civility, and by doing so buttresses Canada’s unchanged status as a settler colonial state. I track and evaluate ruptures in the show's civil language and decorum by reading moments of debate when the logical foundations of these stereotypical national narratives are challenged. Thus, this thesis examines not only what panelists say to each other, but also what their dialogue says to other Canadians. I argue that panelists’ critiques of the nation drawn from their readings of the books - readings that are not so much holistic interpretations of books but strategies for winning the Survivor-style game - are welcomed by the show’s annual social justice themes which then use them to purvey the nation’s virtuous liberalism. Ultimately, my analysis traces how the civil protocols of the program through these three seasons reproduce conflicts between Indigenous peoples and Canadians by reinforcing the inequity of the arrangements of the existing nation-state.
Keywords: Canada Reads; Canadian Literature; Indigneous; Settler; Colonialism; Reconciliation; Multiculturalism; CBC